Getting a “Handle” on Holistic Christian Mission: The Contribution of Isaiah 61 as a Discrete Old Testament Voice - Mason, Steven D. (Missiology, 2012)
This study of Isaiah attempts to show that Isaiah 61 reflects a number of ideas indicative of a holistic view of salvation in the eschatological age—an age inaugurated by Jesus. The development of “righteousness” and the “servants of the Servant” themes serve to show that the individual of Isaiah 61 fulfills the high standard on both accounts. Moreover, the mission of the servant in Isaiah 61 is inherently holistic, as had been established early on in the book. This involves the covenant expectation to fulfill a range of righteous actions indicative of the good news of salvation. To argue that Isaiah 61 serves as a paradigm for Christian mission is, on one level, self-evident from Jesus' own reference to the text in Luke 4. However, this essay has a larger hermeneutical point. A Christian reading of Isaiah 61 in its own context complements what we learn from the New Testament's employment of the text. Isaiah 61 reveals a call placed upon all Christians, not just Jesus. This standard for mission is not only achievable by the Spirit of God (Isa 61:1) but is also to be emulated by all servants of the Servant as the progression of the book implies. As Christians pursue holistic, and distinctively Christian mission, the fundamental idea must be recalled—as servants of the Servant Jesus Christ, righteous action, in terms outlined in Isaiah 61 and its context, is a covenant obligation.